2021
DOI: 10.14214/sf.10468
|View full text |Cite
|
Sign up to set email alerts
|

Economic effects of grouse-friendly forest management

Abstract: Traditional timber production may have negative effects on other ecosystem services. Therefore, new forest management guidelines have been developed in order to enhance a habitat suitable for wildlife. In Finland, a recent example of this is grouse-friendly forest management (GFFM) which emphasises the preservation of grouse species (Tetronidae) habitats. This study aimed to analyse the economic effects of these guidelines. An analysis was made on how the application of GFFM affected the Net Present Value (NPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Likewise, our analysis revealed that this deer habitat provision policy is not the cost it is perceived to be in every case. In a study comparing timber harvest management to grouse-friendly management in Finland, researchers found that 30-year net present value (NPV) calculations at very low discount rates resulted in economic benefits to wildlife management in some cases [5]. Similar to our analysis, they found that a non-management parameter (discount rate used) had a large impact on the calculated outcome; in our case, it was site-specific species factors that influenced the results.…”
Section: Solutions Through Managementsupporting
confidence: 73%
See 1 more Smart Citation
“…Likewise, our analysis revealed that this deer habitat provision policy is not the cost it is perceived to be in every case. In a study comparing timber harvest management to grouse-friendly management in Finland, researchers found that 30-year net present value (NPV) calculations at very low discount rates resulted in economic benefits to wildlife management in some cases [5]. Similar to our analysis, they found that a non-management parameter (discount rate used) had a large impact on the calculated outcome; in our case, it was site-specific species factors that influenced the results.…”
Section: Solutions Through Managementsupporting
confidence: 73%
“…Changes may be necessary to accommodate both uses, such as adjusting the timing or intensity of timber harvests, with the potential for resulting financial repercussions. Yet numerous studies worldwide have concluded that habitat maintenance and profitable forest management are not necessarily in opposition [4][5][6][7][8]. In some instances, the perceived costs of meeting wildlife habitat needs on working timberland were overestimated until researchers parsed out the true economic impact [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent Finnish studies, game-oriented forest management has also been called gamefriendly forestry (Haakana et al 2020) and grouse-friendly forest management (Rautiainen et al 2017;Haara et al 2021) and is considered as a rather cost-efficient forestry practice for forest owners (Haara et al 2021). Although it may be impossible to create explicit instructions that are suitable for all forest stands, commonly suggested methods include the preservation of game thickets, favouring mixed tree species distribution, and avoidance of excessive clearing of the underbrush (Melin et al 2020).…”
Section: Available Measures For Grouse Habitat Managementmentioning
confidence: 99%
“…The latter could also benefit from wider client relationships and the larger management units provided by cross-boundary contracts (Meadows et al 2013). Often the stumpage prizes (or price of standing timber) are linked to the size of the sales units (Buongiorno and Young 1984;Sydor and Mendell 2008; see also Haara et al 2021), and in this way, cooperatively managed forests could also benefit forest owners economically.…”
Section: Conditions Based On Service and Policy Adaptationmentioning
confidence: 99%
“…Consequently, the identification of opportunities to compensate for possible losses in net revenues is key to the promotion of lek management in private forests. In general, cost-effective ways to promote the production of ecosystem services can be found by changing the philosophy that underpins forestry practices [20], which can also benefit the habitats of grouse species [21]. In addition, the possibility of receiving payments for ecosystem services [22] could compensate for economic losses, provided these payments are available.…”
Section: Introductionmentioning
confidence: 99%